Pembelajaran Bahasa Arab Bagi Peserta Didik Madrasah Ibtidaiyah sebagai Pembelajar Pemula - Anandyah Nur Aini; Taufik, Taufik (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2024)
This article discusses about Arabic language learning for Islamic elementary school students as beginner learners. In preparing this article, researchers used qualitative research methods with literature study as a data collection technique. Literature study is a data collection technique by studying and understanding literature sources related to the researcher's topic. The literature referred to is in the form of books, journals, articles, theses, previous research or other sources that are still relevant to the topic of Arabic language learning for MI students as beginner learners. This research is motivated by the implementation of Arabic language learning that is not suitable for beginner learners, both in terms of methods, models, stages, or delivery techniques used, as well as the difficulties and challenges experienced by beginner learners in the Arabic language learning process. This study aims to provide views for educators, researchers, or educational practitioners, especially in Arabic language learning about techniques and stages that can be applied to beginner learners. So the conclusion obtained is that learning Arabic for beginner learners requires more optimal efforts compared to advanced learners or even advanced learners, both in terms of preparation and implementation. This is because the structure of Arabic is more complex and very different from other languages, especially writing.